The pedagogical thought of Natalia Górriz (2017)
This article describes and analyzes the work of the first Central American female educator and author of the texts on pedagogy that most influenced students and educators in the early twentieth century. Natalia Górriz was not only a teacher, and the director of the main Teachers colleges in her country, she was also a feminist writer and geographer. Her work integrates key concepts that redefine the teacher's role, one of her most recurrent concerns. In addition to embracing the main ideas of educational psychology of that time, she also presents ideas about the recognition of children´s rights within the school organization. The analysis of her work is based on historical-hermeneutic methods and carried out through a comprehensive compilation of her work written in books and newspaper articles.